꿀벌 꽃가루 열수 추출물의 큰포식세포 면역활성 효과 - 김이은(Yi-Eun Kim); 조은지(Eun-Ji Cho); 변의홍(Eui-Hong Byun) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2018)
Activation of macrophages plays an important role in the host-immune system. In this study, we investigated the functional roles and related signaling mechanism of hot-water extracts of bee pollen (BPW) in RAW 264.7 macrophages. Since BPW did not exert cytotoxicity at concentrations ranging from 62.5 to 250 μg/mL in macrophage cells, a concentration of 250 μg/mL was used as the maximum dose of BPW throughout subsequent experiments. BPW increased inducible nitric oxide synthase-mediated nitric oxide production in a concentration-dependent manner. Additionally, BPW was found to induce macrophage activation by augmenting the expression of cell surface molecules (cluster of differentiation; CD80/86, and major histocompatibility complex; MHC class I/II) and production of proinflammatory cytokines (tumor necrosis factor-α, interleukin-6, and IL-1β) through mitogen-activated protein kinase and nuclear factor-κB signaling pathways in RAW 264.7 macrophages. Taken together, our results indicate that BPW could potentially be used as an immunomodulatory agent.